Creatinine is a biochemical marker for assessing how untrained people adapt to fitness training loads - Chernozub,Andrii; Potop,Vladimir; Korobeynikov,Georgiy; Timnea,Olivia Carmen; Dubachinskiy,Oleg; Ikkert,Oksana; Briskin,Yuriy; Boretsky,Yuriy; Korobeynikova,Lesia (PeerJ, 2020)
Background To study the peculiarities of changes in creatinine concentration in blood serum of untrained men during the prolonged usage of training loads different in volume and intensity, and to determine the value of this biochemical marker for the assessment of adaptive body changes during fitness training. Methods We examined 50 untrained men aged 18–20 years who had no contraindications for practicing fitness. Taking into account the aim of the research, we divided these people into two groups: group A and group B. The research participants used training load regimes different in volume and intensity: representatives of group Aused low intensity training load regime (Ra = 0.53) and representatives of group B used high intensity training load regime (Ra = 0.72). To assess the adaptive body changes in the examined contingent, we used the anthropometry method (circumference body size) and bioimpedansometry (body composition indicators). We also determined the features of adaptation-compensatory body reactions to different training loads by means of biochemical control of creatinine concentration in blood serum. Results The obtained results showed a significant increase in basal level of creatinine concentration in blood serum (by 17.6%) of group B representatives fixed after 3 months of practicing fitness in high intensity training load regime (Ra = 0.72). This group representative also revealed the most pronounced manifestation of adaptive body changes confirmed by the results of the maximal muscle strength growth (1RM) and circumference body size, which was almost 2.5 times higher than the results of group A representatives for the same period of time. The parameters indicating the load volume in a set (Wn) were almost 62.0 % higher in group A representatives in comparison with group B during all stages of control. Nonetheless, the highest creatinine concentration in blood serum (by 11.1 % (p < 0.05) was fixed in group A representatives in response to training load after 3 months of practicing. This fact testifies to the important role of the creatine phosphokinase mechanism of energy supply of muscular activity in the conditions of high volume and low intensity training load regime (Ra = 0.53). Conclusion The analysis of the results obtained during a series of experimental studies indicates the need and feasibility of using the indicator of basal level of creatinine concentration in blood during fitness training, especially in the conditions of high intensity and low volume training load regime (Ra = 0.72), as an informative marker for assessing the process of long-term adaptation.
Keywords: Creatinine concentration in blood serum; Training load regimes; Adaptive body changes; Biochemical control; Fitness